Broileritilojen talous vuosina 1994 - 2000 - Lehmusvuori, Pia (Maatalouden taloudellinen tutkimuslaitos, 1999)
Kotimaisen tuotannon ja kulutuksen markkinatasapaino on osoittautunut EU-jäsenyydessä vaikuttavan olennaisesti tuotannon kannattavuuteen. Erityisen selvästi tämä tulee esille tarkasteltaessa sitä, miten siipikarjatalous on sopeutunut Suomessa EU-jäsenyyteen. Broilerinlihan tuotanto on kasvanut kysynnän kasvua vastaavasti ja tuottajahintataso on säilynyt hyvänä verrattuna muihin EU-maihin. Kananmunien voimakas ylituotanto ja kysynnän heikkous puolestaan romahduttivat niiden tuottajahinnan verraten alhaiselle tasolle. Selvityksessä on tarkasteltu viljelijäperheen työlle ja pääomalle korvaukseksi jäävää maataloustuloa broilerituotannon osalta erillään tilan muusta maataloustuotannosta. Broileritilojen tuotannon laajentumisesta johtuen broilerituotannon maataloustulo kasvoi vuosina 1994-1997 noin 4 %, mutta teurasbroileria kohti tulo aleni 12 %. Kyselyyn osallistuneilla kananmunatiloilla koko tilan tuotantoa koskeva maataloustulo oli vuonna 1997 noin puolet pienempi kuin vuonna 1994. Ilman kansallisen tuen jatkomahdollisuutta vuonna 2000 AB-alueella maataloustulo jäisi noin kolmasosaan vuoden 1994 tasosta. C-alueella maataloustulo olisi pohjoisen tuen ansiosta vuonna 2000 noin kaksi kolmasosaa vuoden 1994 tasosta. Tiedot käyvät ilmi MMM Pia Lehmusvuoren laatimasta Maatalouden taloudellisen tutkimuslaitoksen raportista "Siipikarjatilojen talous vuosina 1994-2000". Tutkimus perustui viljelijäkyselyyn, jossa oli mukana runsaat 50 broilerintuotantoon ja 60 kananmunantuotantoon erikoistunutta tilaa.

The purpose of the study was to examine broiler production in Finland, investments in broiler husbandry as well as intentions concerning such investments. The another aim was to calculate income development in broiler production in 1994, 1996 and 1997 on the basis of the taxation data and also an estimate was made concerning income development in 1998 - 2000. The data were collected by means of an informed questionnaire, and the number of broiler producers who replied was 53. Depending on the year, the income development in broiler production was examined from the data of 37-41 farms, which were weighted by the number of broiler farms in each size class in 1995. Besides that the result of all agricultural production on broiler farms in 1994 - 1996 was examined on the basis of the average weighted taxation data from 36-45 broiler farms included in the Enterprise and Income Statistics of Agriculture and Forestry. Most of the farms participating in the study intend to continue broiler production, but about a fifth of the entrepreneurs can be considered to express some uncertainty in terms of this. Two thirds had invested in broiler production in 1995 - 1997. The investments mainly concerned feeding, air conditioning or heating. About a quarter of the farms had built a new production building or extended the old one. According to the study, the willingness to invest continues in 1998 - 2002. Almost an half of those who replied intended to invest in new or existing broiler production buildings. One out of four farmers were uncertain in terms of future investments and one out of ten had no intentions to invest in broiler production. In 1997 an average broiler farm, with about 139,000 broilers slaughtered, agricultural income from broiler husbandry amounted to about FIM 195,000. Before the EU membership in 1994 agricultural income was almost the same even if the number of broilers was 18% smaller. The trends were proportionally the same in the case of the development of the income from all agricultural production on broiler farms included in the Enterprise and Income Statistics of Agriculture and Forestry in 1994 - 1996. As a result of the decrease in the transitional aid paid in 1995 - 1999, the agricultural income in broiler production would fall by a third in 1998 and in 1999 by more than half from the level of 1997. According to the current provisions, in 2000 broiler production in support areas A and B would no longer be eligible for national aid, and in such a situation the incomes would not even cover the costs of broiler production. If the amount of aid stayed at the level of 1999 in support area C1, where the northern aid can still be paid, agricultural income in this region would remain about FIM 84,000 per farm. Finland negotiates with the EU in 1999 on the possibilities to continue the aid for livestock production in areas A and B. The sensitivity analysis shows that the development of the sales income from broiler meat and expenditure in purchased fodder are even more significant in terms of the income development in broiler production than the levels of aid. Because of the importance of the sales income and the establishment of the producer price on the market broiler production is highly sensitive to economic fluctuations. The balance between the production and consumption is thus decisive in terms of maintaining stable producer prices.
Economy of broiler farms in 1994 - 2000
Keywords: Ma; Ko; broileritilat; broilerituotanto; tuotannon jatkaminen; tulokehitys; siipikarjatilat; siipikarjanlihantuotanto; broilerit; investoinnit; maataloustulo; poultry; farm income; broiler farms; agricultural income; investments; continuation of production; income development